Predictors of exaggerated blood pressure response to aerobic exercise in obese adolescents - L. V. Danilyuk (Scientific Сentre for Family Health and Human Reproduction Problems, 2016)
Association of blood pressure response during exercise of cardiometabolic risk factors (CMRF) is demonstrated in adults. The objective was to determine predictors of raised exercise blood pressure (BP) response during aerobic exercise in obese adolescents. The maximal treadmill test using the Bruce protocol was performed in 82 normotensive obese adolescents (12-17 y.o., 43 boys). Adolescents were divided into 2 groups: group 1 (n = 68) - children with normal BP response to exercise; group 2 (n = 14) - adolescents who had excessive increase in systolic BP (SBP) during exercise. We used logistic regression analysis to examine the associations between cardiometabolic risk factors (CMRF) and SBP response during exercise with adjustment for baseline SBP, sex, age and duration of exercise test period. We have found exaggerated BP response to exercise in 17.1 % of patients. In adolescents of group 2 baseline SBP was higher than in group 1 (p = 0.01). Glucose level and lipid metabolism disturbances, SDS Z-score, baseline SBP levels only by 24.8 % explained the formation of the hyperreactive SBP response to exercise (χ2 = 13.2; р = 0.068). Only baseline SBP was an independent predictor for exaggerated BP response (p = 0.025) and age was a significant trend towards influence (p = 0.054). Exaggerated BP response to exercise in normotensive obese adolescents is more common for older adolescents who have baseline SBP levels in the range of elevated normal values. Knowing CMRF as well as the degree of excess weight has no effect on excessive BP rise during exercise.